EU Regional Policy: Vertical Fiscal Externalities and Matching Grants - Robert Fenge; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2004)
Although decision processes at the EU level are highly complex and often require unanimity, explicit side payments among member states are unknown. However, logrolling and redistributive policies are substitutes. This paper considers the EU regional policy as a substitute for explicit side payments and asks - from a normative and a positive point of view - why matching grants instead of unconditional grants are used although at first sight regional policy is a national and not a union-wide task. It argues that the EU system of own resources creates positive vertical fiscal externalities. Hence, matching grants are part of an efficient grant system and, in so far as bargaining in EU bodies is efficient, matching grants are the natural outcome.
Keywords: H54; H77; H87; 330; European economics; regional policy; intergovernmental grants; side payments; vertical fiscal externalities